2016
DOI: 10.1093/gerona/glw125
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular to Intracellular Water Ratio in Upper Legs is Negatively Associated With Skeletal Muscle Strength and Gait Speed in Older People

Abstract: Skeletal muscles contain a large volume of water that is classified into intracellular (ICW) and extracellular (ECW) water fractions. Nuclear magnetic resonance-based biomarkers suggest that increased water T2 heterogeneities, as well as elevated water T2 relaxation in the quadriceps occurs in the elderly when compared with young adults. However, nuclear magnetic resonance is difficult to apply to a large-scale study or a clinical setting for sarcopenia and frailty screening. Segmental bioelectrical impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 48 publications
10
86
1
Order By: Relevance
“…that included men and women with mean group ages in the seventh or eighth decades. Skeletal muscle mass or size was estimated in these studies using ultrasound or BIA prediction formulas . Phase angle was not specifically measured in these studies, rather quality indices calculated at different frequencies or predicted values for extracellular and intracellular water were derived from bioimpedance spectroscopy measurements .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…that included men and women with mean group ages in the seventh or eighth decades. Skeletal muscle mass or size was estimated in these studies using ultrasound or BIA prediction formulas . Phase angle was not specifically measured in these studies, rather quality indices calculated at different frequencies or predicted values for extracellular and intracellular water were derived from bioimpedance spectroscopy measurements .…”
Section: Discussionmentioning
confidence: 99%
“…Peak torque through extension was measured in Newton‐metres and taken as the maximum torque achieved during the three sets. We refer to this measurement as leg strength, although it has also been termed knee extension strength . The CV for leg strength measurements was 6.1%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance of intracellular water (R ICW ) and extracellular to intracellular water ratio (ECW/ICW) were calculated using the following equations (Yamada et al, 2017): Resistance of intracellular water (R ICW ) and extracellular to intracellular water ratio (ECW/ICW) were calculated using the following equations (Yamada et al, 2017):…”
Section: Measurement Of Bioelectrical Impedancementioning
confidence: 99%
“…One of the most wellknown equations for estimating muscle mass by BIA was developed by Janssen et al using MRI as follows: SMM (kg) = ((Ht 2 /R50 × 0.401) + (sex × 3.825) + (age × −0.071)) + 5.102 [30], and many BIA equations are age-dependent. Yamada et al indicated that expansion of ECW relative to ICW or total body water (TBW) is observed with aging, and may mask actual age-related decrease of muscle cell mass [32,34,[39][40][41]. The Z at low-frequency (≤50 kHz, for example, Z5 or Z50) currents mainly reflects ECW.…”
Section: Multi-frequency Bioelectrical Impedance Analysismentioning
confidence: 99%